(untitled) (Balneo and PRM Research Journal, 2021)
The purpose of this paper is to point out and propose the most effective means of therapeutic swimming in the use of work programs for patients with dorsalgia in spinal static disorders. The knowledge degree of therapeutic swimming is not sufficiently promoted and used, which is why we propose the following hypothesis: we start from the premise that therapeutic swimming can reduce the dorsalgia in the spine, improve lung capacity and physical condition in young adults. The objectives of this work are to identify subjects with spinal static dorsalgia and to establish the sample for the experiment; in the selection of therapeutic swimming means for the elaboration of the work program; in the registration and interpretation of the data in the form of tables and charts. The experiment took place at the Kinetic Therapy Practice of Mr. Constantinescu Mihai, as well as at the swimming pool in Cornisa, Botoşani county, with a sample consisting of 15 subjects aged between 18 and 22, all of whom suffered dorsalgia (in the spine). In this respect, we set out to implement a therapeutic swimming program for 6 months to achieve positive results.